ISLAMIC EDUCATION MODEL BASED ON COMMUNITY DEVELOPMENT - Muhammad Reza Bakhtimi; Zamroni Zamroni; Wahdiansyah Wahdiansyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Islamic education plays a strategic role in shaping perfect human beings and as a driving force for just social change. The dynamics of contemporary society demand an Islamic education model that emphasizes not only the transfer of religious knowledge but also focuses on community empowerment. This study aims to examine and formulate a conceptual model for Community-Based Islamic Education (PIBPM) through a library research approach. Data sources include primary and secondary literature such as scientific journals, books, and educational policy documents. The results indicate that PIBPM must be based on the values of the caliphate, amar ma'ruf nahi munkar, and social justice. Implementation of this model requires the integration of a community-based curriculum that is contextualized to local needs and wisdom, active community participation as educational subjects, and strategic collaboration among stakeholders. Islamic educational institutions need to transform into centers of social, economic, and spiritual empowerment. Thus, PIBPM not only strengthens the relevance of Islamic education to social development but also affirms its role as an agent of transformation towards an empowered and civilized society.